India Unbound
India today is a vibrant free-market democracy and has begun to flex its muscles in the global information economy and on the world stage. Now, acclaimed columnist Gurcharan Das traces India's recent social and economic transformations in an eminently readable, impassioned narrative. Das tells the stories of the major players in a period of rapid and profound change -- from schoolchildren inspired by Nehru's speeches in the early days of Independence to the current software impresarios -- and makes comprehensible and compelling the economic and political development responsible for these changes. He weaves his personal story into the larger context of contemporary history: his family's move to America in the mid-1950s, his education at Harvard, his years in India as a young marketing executive wrestling with a socialist system he feared would undermine the country's vast potential. He also shows us the reasons behind his optimism for his nation's future, among which is the exciting landscape of information technology today. Das argues that the changes of the past fifty years have, at last, amounted to a revolution -- and it is one that has not been chronicled before. With India Unbound, he gives us a book that is at once vigorously analytical and vividly written -- an essential insider's road map to India, then and now.